Study of the pattern and management of blunt chest injuries in rural setup - Sharma, Kuldeep; Pradeep Tated, Sushrut; Ashokrao Hatkar, Ashish (International Surgery Journal, 2017)
Background: Trauma is recognized as a serious public health problem. In fact, it is the leading cause of death and disability in the first four decades of life and is the third most common cause of death overall. Trauma may lead to short or long-term disability. Objective was to study the pattern of chest injuries with resultant underlying damage, in rural set up. Methods: The present study was carried out among 500 cases of age group 15 to 75 years, all religions and both sexes. All patients received in the Emergency Room (ER/Casualty) were immediately attended and history, primary survey and resuscitation were done simultaneously. X ray chest-erect position was taken and subsequent management either operative or non-operative was done according to clinic-radiological findings. After discharge, patients were followed on OPD basis till the time they return to the normal activity. Results: Majority of patients (31%) were from 55 to 65 years of age group and were male (64.2%). Vehicular accident was the commonest (56.8 %) cause of injury. Vehicular accidents were the most common cause of chest injuries. In vehicular accidents two-wheeler riders were the common victims (55.28%). Assault was 2nd most common mode of injury. Among those patients who sustained chest trauma had average VAS 6 (49.2%) followed by 4 (45%). Majority of patient were treated conservatively (93.6%). Conclusions: The most active age group and males were affected with commonly vehicular accidents. They mainly suffered chest injuries.